ENERGY REVOLUTION UNDER THE BRICS NATIONS - M. K. Sahu (BRICS Law Journal)
The BRICS countries are of critical importance to both supply and demand fundamentals of energy markets globally. Today BRICS plays a very important role in the system of international energy security. BRICS energy diversification is driven by concerns for energy security. The potential for a BRIC energy partnership is thus enormous. The development of the BRIC countries in the next coming decades will include demographic changes with a growing middle class population which will demand more energy and resources that our world has the potential to supply.A Green Energy Revolution is the panacea to solve major social, economic and environmental effects of their growing populations. This paper is an attempt to highlight the cooperation among the BRICS Nations for the development of Energy Sector and at the same time the concerning issue of climate change etc. It further discusses about the contribution of BRICS countries in the global economy. This paper also discusses about the role of the BRICS Nations in collaboration with the International Energy Agency.